Peng ancestral hall in the Guangfu region: Social memory, bodily practices, and cultural revitalization in the process of moderniz - Guang, Hui; Phanlukthao, Peera (Edelweiss Applied Science and Technology, 2025)
This study explores the transmission of cultural heritage and the construction of social memory at Peng Ancestral Hall in the Guangfu region, utilizing the frameworks of bodily practice and social memory. The research aims to: (1) trace the historical evolution of Peng Ancestral Hall; (2) analyze its artistic techniques and cultural functions; (3) examine the interplay between bodily practices and social memory; and (4) design and implement innovative cultural heritage activities. A qualitative approach was adopted, incorporating literature reviews, interviews, field observations, and textual analysis, alongside practical cultural activities. Findings reveal that Peng Ancestral Hall reflects the historical evolution of ancestral hall culture through its architecture and murals, which blend traditional themes with Western artistic influences, fostering intercultural understanding and familial ethics. Bodily practices and social interactions within the hall transform individual memory into collective memory, reinforcing family cohesion and cultural continuity. Innovative activities, such as mural creation and ceremonial practices, engage younger generations, revitalizing the hall’s role in cultural education and community engagement. Participants reported heightened cultural identity and appreciation for tradition. The study concludes that Peng Ancestral Hall successfully balances historical preservation with modern cultural innovation, offering insights into safeguarding intangible heritage and promoting local cultural tourism.